Indium Tin Oxide Nanoparticles Formation for Organic Electronics - Yu, Hyeonghwa (My University, 2016)
Indium tin oxide is a transparent conductive oxide electrode which is widely used for organic electronics. Morphology of ITO plays an important role in the performance of organic electronics. To understand the influence of the substrate morphology in device performance, a controllable route for producing periodic and aperiodic roughness of ITO surfaces are necessary. In this thesis, this was attempted by using various approaches to forming ITO nanostructures. Initially, ITO was deposited by a traditional sputtering procedure. However, the roughness distribution of the sputtered ITO resulted in a s Gaussian distribution, unsuitable to further studies of roughness. ITO nanostructures can also be formed by depositing ITO nanoparticles on an ITO sub- strates. Using acetate and chloride precursors, ITO films were produced from solution and formed into nanoparticles using the reverse micelles deposition approach. The acetate route (InAc+SnCl2+ethanol), was the most successful prior to the nanoparticle formation, showing high quality ITO with bixbyte crystal structure and Sn percentages of 20%, low enough to form a conductive film. Nanoparticles were fabricated with diblock copolymer reverse micelles(PS-b-P2VP). Reverse micelles were found to act as a nano reactor, restricting the size of nanoparticles by having hydrophilic reactants undergo chemical reactions inside the micelles. However, nanoparticles from the reverse micelles revealed Sn percentages much above 20%. This was attributed to the solubility difference of the precursors leading to displacing or preventing of pre- cursor loading into the reverse micelles. The change of the stirring time, the micelles concentration, the sequence of precursors loading, and the weight of precursors were not found to affect the Sn concentration; moreover, large variations in Sn concentrations were observed. From quantitative nano mechanical testing of the micelles, a maximum load amount for the precursors was observed, confirming that the high concentration of Sn was likely due to the solubility differences between the precursors and their ability to penetrate the micelle. By manipulating the nanoparticles distribution through spin coating speeds, micelles concentration, and deposited volume, several degrees of order were obtained, though hexagonal packing was not observed. In general, even though Sn concentration were found to be above 20%, nanoparticles were successfully fabricated with reverse micelles, confirming that the reverse micelle technique is a good strategy for future studies of roughness.
Keywords: Indium Tin Oxide; Organic Electronics; Diblock copolymer; Nanoparticles